Plasma High Molecular Weight Kininogen Concentration in Health and in Chosen Impairments of Haemostasis. Evidence that Plasmin Uncovers a New Antigenic Site in High Molecular Weight Kininogen - Kleniewski, Józef (Thrombosis and Haemostasis, 1979)
High molecular weight kininogen (HMW-kininogen) concentration was measured in the plasma of healthy blood donors, patients with haemophilia A, idiopathic thrombocytopoenic purpura, deep vein thrombosis treated with oral anticoagulants and patients treated with streptokinase (SK). The concentration of HMW-kininogen in the plasma of healthy subjects was 92 ± 15 μg/ml. The values obtained in patients’ plasma were not different statistically. In the plasma of patients treated with repeated infusion of SK, a significant increase of HMW-kininogen antigen activity was noted after each injection of the drug. Similar results were obtained when SK was added to plasma “in vitro” or when a purified preparation of HMW-kininogen was treated with plasmin. These and additional data obtained suggest that plasmin uncovers in the HMW-kininogen molecule a new antigenic site(s) common to HMW-kininogen and low molecular weight kininogen and new antigenic site(s) specific only for HMW-kininogen.